A carrier free photodynamic oxidizer for enhanced tumor therapy by redox homeostasis disruption. (18th February 2022) - Yang, Ni; Zheng, Rong-Rong; Chen, Zi-Ying; Wang, Rui-Xin; Zhao, Lin-Ping; Chen, Xia-Yun; Chen, Lei; Xu, Lin; Li, Shi-Ying; Chen, A-Li
Abstract : In this work, we developed a carrier free photodynamic oxidizer to decrease intracellular glutathione (GSH) levels and disrupt the redox homeostasis for enhanced photodynamic therapy (PDT) efficacy on tumor inhibition. Abstract : Abnormal tumor microenvironments play important roles in cancer progression. In general, tumor cells are capable of upregulating glutathione (GSH) levels to maintain aberrant redox homeostasis and cause resistance to oxidative damage. Herein, we develop a photodynamic oxidizer to disrupt the redox homeostasis of tumor cells for enhanced photodynamic tumor therapy. Based on pyropheophorbide-a (Pyro) and naphthazarin (Nap), a carrier free photodynamic oxidizer (named PyroNap) is prepared by the self-assembly technique through hydrophobic interactions. It is confirmed that nanosized PyroNap has high drug contents as well as favorable dispersity and stability. Besides, the photodynamic property of Pyro has obviously improved after self-assembly into the nanomedicine of PyroNap, which facilitates the production of reactive oxygen species (ROS) for robust photodynamic therapy (PDT). More importantly, the Nap induced GSH decrease could disrupt the redox homeostasis of tumor cells to further improve the PDT efficacy on tumor suppression. Consequently, after intravenous administration, PyroNap was able to significantly inhibit tumor growth and cause minimal side effects. This study might shed light on developing translational nanomedicine for tumor precision therapy.